Applied latent class analysis - Hagenaars, Jacques A.; McCutcheon, Allan L., 1950-2016 (Cambridge University Press, 2002)
Applied Latent Class Analysis introduces several recent innovations in latent class analysis to a wider audience of researchers. Many of the world's leading innovators in the field of latent class analysis have contributed essays to this volume, each presenting a key innovation to the basic LCM.